Una comparativa dels conceptes 'Espanya' i 'Catalunya' a inicis del segle XVIII: El seu ús en els Dietaris institucionals de Barcelona i del General de Catalunya. - PALOMO REINA, CRISTIAN (Scripta, 2019)
In this article we will carry out a quantitative, semantic and comparative analysis of the concepts 'Spain' and 'Catalonia' in its singular and plural forms of the Catalan, Spanish and Latin languages, contained in the institutional diaries of the Consell de Cent of Barcelona and the Deputation of the General of Catalonia. The chronology analysed will be the start of the 18th century, a period in which the death of the Spanish monarch Charles II of Austria (1700), the enthronement of the Bourbons (1701) and the consequent war of succession for the Monarchy of Spain (1702-1715) that was fought in the Principality of Catalonia between 1704 and 1714. The results of the study offer new perspectives on some aspects of the historiographical debate unleashed by the celebration of the Tricentenary of 1714, which revolves around the collective identity of Catalans at the beginning of the 18th century.